Rural transformation in central Myanmar: By how much, and for whom?. (April 2019) - Belton, Ben; Filipski, Mateusz
Abstract: Rural Southeast Asia is undergoing a series profound changes, often referred to as 'rural transformation', but recent research is divided as to whether rural transformation is underway in Myanmar. This paper addresses two empirical questions. (1) Is rural transformation taking place in Myanmar? (2) How has rural transformation affected the welfare of rural households in Myanmar's Central Dry Zone? We find evidence of significant rural transformation happening in the Dry Zone. The following features stand out: First, there has been a shift in relative economic status and power between landholders and the landless, in favor of the latter. This rebalancing has occurred mainly due to rising rural wages linked to rapid migration to urban areas. Second, widespread agricultural mechanization has taken place over the same period as migration. However, despite generating some labor savings for farm households, the labor productivity boosting effects of farm machinery appear to have produced insufficient gains to offset the effects of rural wage increases. Third, migration appears to offer the prospect of greater social and economic mobility to landless and marginal farm households. For all groups of households, including the landless, remittance incomes have more than offset income earning opportunities lost in agriculture due to mechanization. Fourth, landownership patterns, gender relations, and the extent of agricultural commercialization all appear largely unaffected by these changes. Highlights: We find evidence of rapid transformation in Myanmar's Dry Zone over the past decade. Agriculture has mechanized rapidly, causing a decline in demand for agricultural labour. Remittances and rising rural wages have more than offset labour incomes forgone. The position of landless and land-poor households is improving relative to farm households. Patterns of landholdings and gender relations appear relatively unchanged.